(3NdGUI GdeaGNQ hENJUGQ efGbH GdTjN YHOGdbGOQ hLeGYI eef YXeg ef GdTjhN GdCcGHQs - (3Yaja GdOjf YHO Gddg Hf CSYO Hf Ydj GdjGaYj Gdjefjs; (3GdjGaYj , Yaja GdOjf YHO Gddg Hf CSYO Hf Ydj GdjGaYj Gdjefj, Yaja GdOjf,J (B768 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg JYGdi agPG cJGH YLGFH GdBjGJ GdeTJedGJ Ydi ZQGFH GdcQeGJ GdJi gi ef JJeGJ GdeYLRGJ hGdHQGgjf CQOaJgG Ydi SHjd GdJcedI dcJGHj GdehShe HQhV GdQjGMjf hdbHJg NdGUI GdeaGNQ s
(3BNQgG (B:s
(3hSHMGfc Gddge QHkG ebOSkG hChSY bWQ ddhQi aVdg ehdi s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs